Leptospirosis as a risk factor for chronic kidney disease: A systematic review of observational studies - Carrillo-Larco, Rodrigo M.; Altez-Fernandez, Carlos; Acevedo-Rodriguez, J. Gonzalo; Ortiz-Acha, Karol; Ugarte-Gil, Cesar (PLOS Neglected Tropical Diseases, 2019)
Author summary Leptospirosis is an infection that can affect the kidneys acutely, though it seems that even after the acute infection there could be risk of a long-term impaired kidney function. The evidence on this matter is sparse and limited, thus the need to comprehensively seek, synthetize and appraise the available scientific literature. In so doing, this work has found preliminary evidence that leptospirosis may be associated with impaired kidney function as per eGFR. This work and findings strongly reveal that more research is needed to quantify and characterize the long-term risk of CKD among those who had had leptospirosis infection. The raising burden of non-communicable diseases paired with a still non-negligible burden of communicable and neglected tropical diseases in low- and middle-income countries, deserve the synergism of these two broad fields for the benefit of patients and population health.